Extracellular polysaccharide production by a novel osmotolerant marine strain of Alteromonas macleodii and its application towards biomineralization of silver. - Ananya Mehta (Public Library of Science (PLoS), 2014)
The present study demonstrates exopolysaccharide production by an osmotolerant marine isolate and also describes further application of the purified polysaccharide for production of colloidal suspension of silver nanoparticles with narrow size distribution. Phylogenetic analysis based on 16S r RNA gene sequencing revealed close affinity of the isolate to Alteromonas macleodii. Unlike earlier reports, where glucose was used as the carbon source, lactose was found to be the most suitable substrate for polysaccharide production. The strain was capable of producing 23.4 gl(-1) exopolysaccharide with a productivity of 7.8 gl(-1) day(-1) when 15% (w/v) lactose was used as carbon source. Furthermore, the purified polysaccharide was able to produce spherical shaped silver nanoparticles of around 70 nm size as characterized by Uv-vis spectroscopy, Dynamic light scattering and Transmission electron microscopy. These observations suggested possible commercial potential of the isolated strain for production of a polysaccharide which has the capability of synthesizing biocompatible metal nanoparticle.